Rapid Assessment of the Horticulture Industry in Moldova - World Bank (World Bank, Washington, DC, 2017)
The Rapid Assessment of the Horticulture Sector in Moldova was conducted as part of the Moldova Food Security Technical Assistance (TA), financed from the Global Food Crisis Response Program (GFRP) trust fund (TF). The original aim of the TA was to inform the formulation of the government’s food security strategy and the reform of related policies, with a view towards a paradigm shift from a self-sufficiency and production volume oriented to a competitiveness-based agricultural policy framework. Agri-food trade vulnerabilities were most recently exposed in the current regional geopolitical context, which led the Russian Federation impose an import ban on key Moldovan agricultural products (wines, meat products, fruit and vegetables) through 2013 and 2014. More than half of Moldova’s agri-food exports go to CIS countries (predominantly Russia)1, and another third to the EU. Much higher levels of agricultural subsidies in other markets, particularly in the EU, undermine the competitiveness of Moldova’s agri-food products on both foreign and domestic markets. Furthermore, despite the recently adopted Deep and Comprehensive Free Trade Agreement (DCFTA) with the EU and despite an increase of the European import tariff rate quotas, the Moldovan products were not able to find immediate outlets on the EU market. The main reasons stemmed from a lack of adaptation to or compliance with European market quality and phytosanitary standards. The Rapid Assessment of the Horticulture Sector in Moldova, carried out between September 2014 and March 2015, serves a dual purpose: (i) provide an overview of the strengths as well as weaknesses of the Moldovan horticulture sector, which constitutes a vital component of the country’s agricultural economy and rural society, and (ii) explore opportunities for fruit and vegetables market and product diversification, which could reduce some of the observed sector vulnerabilities.